(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The purpose of research is to know the government’s strategy in improving tourism development in North Bolaang Mongondow district. The study uses qualitative approach methods. The informant is the head of tourism Department of 1 person, head of section 3 persons, staff/officers of Tourism Office 4 persons, community/Tourist 7 people so total informant there are 15 persons. Data collection using interview guidelines, while the analytical techniques used are interactive model analyses of Miles and Hubernan. Based on the results of the research that has been done by the authors, it can be concluded as follows: It can be drawn some conclusions as follows: (1) SO strategy (Strength and opportunities) using the appropriate promotional media target according to the market that will be addressed by the tourism agency so that the right target and continue to be done will intensively produce excellent results. Innovate and explore more types and destinations of tourism objects offered and committed to provide the best service to consumers to maintain the good image of tourism in the eyes of consumers. (2) The strategy of ST (strength and treats) Bolmut Regency government can offer interesting and promising new things with the presentation of quality of natural resources and the interesting tour. Related to changes in the price and tariff charged can be informed through the means of promotion and description of tourist attractions in the media and Disarana and facilities in the attraction. Do not forget to also increase other innovations related to tourism such as creativity in the manufacture of OLE-ole or fruit. (3) The strategy of WO (weakness and opportunities) to ensure that the tariff or charges on similar tourism objects will be the way to overcome the existing threats. In addition, the training and education provider to the community related to tourism management is also very needed. Do not forget to add facilities and supporting facility and recycle or rerejuvenation existing facilities and amenities to make it look more attractive. (4) The strategy of WT (weakness and treats) enhances the safety and comfort of tourists who come to visit. To establish competitive price but not detrimental for tourism and community office. Care and maintenance must be routinely run on every attraction Keywords: Strategy, Government, Tourism Development